An Analysis of Teaching and Learning Variations based on Bloom's taxonomy - Aliyah Nushaibah; Elfrida Elfrida; Dedi Sofyan (Universitas Bengkulu, 2021)
This research aimed to find out the variations of teaching and learning based on Bloom’s Taxonomy, this research focused on the classroom learning activities in the lesson plans. This research employed a descriptive qualitative study. The subject of the research was nine lesson plans that developed by teahers at SMPIT IQRA. The data of this research was the classroom learning activities were classified the variations of teaching and learning based on Bloom’s Taxonomy stated in the 2013 Curriculum. The first finding showed that, there were some variations in classroom learning activities of lesson plans. By three domains of learning based on Bloom’s Taxonomy, those are Cognitive, Affective and Psychomotor. The teachers were fulfilled the criteria of learning activities in lesson plans. But, the lesson plans still need to increase and remake the team of lesson plans system, because the lesson plans that used by teachers were same to each class in the same level.